МОНГОЛ ҮҮЛДРИЙН АЗАРГАНЫ ТӨМСӨГНИЙ МОРФО-ГИСТОЛОГИЙН СУДАЛГААНЫ ЗАРИМ ҮР ДҮН - Бадамханд, Г; Самданжамц, Д (Proceedings of the Mongolian Academy of Sciences, 2016)
The present study aimed to investigate correlation between testicle and body weights, cross section of seminiferous tubule and relationship between the Sertoli cells and matured sperms in stallion of Mongolian breed. It was found that there is significant difference (p<0.001) in testicle weights depending on ages of stallions (121.1 g at 36 months old age and 169.2 g at 48 months old). Changes in the body and testicle weights of stallions to be used for breeding are significantly different at two age classes. There were moderate (r=0.59) and strong (r=0.72) correlations at the ages of 36 and 48 months respectively. Both the testicle weight and diameter of seminiferous tubule increases in mutually related ways and tubule diameter was 72.6 µm and 94.8 µm at 36 and 48 months of stallions age respectively. Sertoli cells play key role in production of sperms from primordial germ cells in the testicle. Interrelationship between Sertol cells and mature sperms in seminiferous tubule is moderate (R2=0.316) and satisfactory (R²=0.445) correlations at 36 and 48 months of ages and it demonstrates differences between the ages are stable.